Enhancement of Doxorubicin Efficacy by Bacopaside II in Triple-Negative Breast Cancer Cells - Sima Kianpour Rad; Kenny K. L. Yeo; Runhao Li; Fangmeinuo Wu; Saifei Liu; Saeed Nourmohammadi; William M. Murphy; Yoko Tomita; Timothy J. Price; Wendy V. Ingman; Amanda R. Townsend; Eric Smith (Biomolecules)
Background: Triple-negative breast cancer (TNBC) is an aggressive subtype with limited treatment options and high resistance to chemotherapy. Doxorubicin is commonly used, but its efficacy is limited by variable sensitivity and resistance. Bacopaside II, a saponin compound, has shown anti-cancer potential. This study evaluates the effects of doxorubicin and bacopaside II, both individually and in combination, across TNBC subtypes to explore mechanisms of resistance and enhanced drug efficacy. Methods: The growth-inhibitory effects of doxorubicin and bacopaside II were assessed in four TNBC cell lines. IC50 values were determined using dose–response assays, and doxorubicin accumulation was measured via spectral flow cytometry. ATP-binding cassette (ABC) transporter expression (ABCB1, ABCC1, ABCC3, and ABCG2) was analyzed for correlations with drug sensitivity. In silico docking assessed the binding affinity of bacopaside II to ABC transporters. A 3D culture model simulated drug-resistant TNBC, and combination effects were evaluated with live-cell imaging. Results: Doxorubicin sensitivity varied across TNBC molecular subtypes, correlating to intracellular accumulation. Bacopaside II inhibited growth across subtypes, inducing apoptosis in sensitive cells and necrosis in resistant cells. Bacopaside II increased doxorubicin accumulation, independent of P-glycoprotein (ABCB1), possibly through interactions with other ABC transporters. In drug-resistant 3D cultures, bacopaside II maintained efficacy and enhanced doxorubicin accumulation, counteracting ABC transporter-mediated resistance. The doxorubicin and bacopaside II combination showed synergistic growth inhibition. Conclusions: Bacopaside II enhances doxorubicin efficacy in TNBC by increasing drug accumulation and overcoming ABC transporter-mediated resistance, suggesting its potential as an adjuvant in TNBC treatment. These findings support further investigation of bacopaside II, particularly for resistant TNBC subtypes.